Sintesis Metil Ester dari Minyak Biji Kemiri (Aleurites Molluccana) Menggunakan Metode Ultrasonokimia - Aziz, Rahmawati; Aisyah, Aisyah; Ilyas, Asriani (Al-Kimia, 2016)
Using the fuel oil is the basic necessary in the world now. But, the raw material cannot be updated. To ensure the availability of the fuel oil so, the newest of alternative energy is explored it. One of the ways is biodiesel which made from vegetable oil. In this research is resulted from the transesterification reaction between candlenut oil and methanol by utilizing ultrasonic equipment. This research has passed some phases, they are the determining of acid number in oil then continued by creating biodiesel from ultrasonic wave 47 kHz. Identification of FTIR and GCMS are two methods which used to analyze the component compound in biodiesel product. The conversion number that be gotten from FAME with reaction of variation time 30, 40 and 50 in succession 0,037%, 0,029% and 0,018%. The result analysis of FTIR shows some of functional groups which are special from biodiesel. While the result of GCMS analysis is known that there are 5 component compounds in biodiesel namely ester methyl palmitic acid, ester methyl olead, stearata ester methyl, linoleic ester methyl and elaidic ester methyl.